Manufacturing method of anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material and rare earth permanent magnet material
The method enhances the magnetic properties and production efficiency of anisotropic rare earth permanent magnets by aligning nanocrystals through specific thermal deformation processes, addressing the limitations of existing methods.
Patent Information
- Application Number
- JP2024536299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-11-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-11-24
AI Technical Summary
Existing methods for producing anisotropic rare earth permanent magnets face challenges in improving magnetic properties, simplifying the production process, and enhancing efficiency, particularly due to issues like residual stress, complex processes, and low coercive force.
A method involving the production of precursor sheet-shaped nanocrystalline magnetic powder, followed by heat deformation processing and orientation treatment, and optional orientation optimization, which includes incubating raw materials at specific temperatures and applying thermal deformation techniques like hot rolling, hot pressing, or hot extrusion to align nanocrystals, resulting in an anisotropic sheet-like nanocrystalline rare earth permanent magnet material.
The method achieves high magnetic properties with B_r of 14.1kGs or more, H_cj of 13.2kOe or more, and (BH)max of 45.7MGOe or more, while simplifying the process and improving production efficiency, making it suitable for industrial mass production.
Smart Images

Figure 2024546159000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application filed with the China Patent Office on November 25, 2022, bearing application number CN202211487970.X and entitled "Method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnetic material and rare earth permanent magnetic material", the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the technical field of rare earth permanent magnet materials, and in particular to a manufacturing method for anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material and the rare earth permanent magnet material. [Background technology]
[0003] Due to its excellent magnetic properties, RE-Fe-B rare earth permanent magnet materials have become an important foundation for the development of high-tech industries, clean energy industries, etc., and are essential functional materials for supporting the implementation of national strategies such as "Made in China 2025" and "Internet +".
[0004] RE2Fe in RE-Fe-B permanent magnet material 14 B phase has a tetragonal crystal structure and has strong uniaxial anisotropy. Ideally, the magnetic properties of anisotropic permanent magnet materials are twice as high as those of isotropic permanent magnet materials. Anisotropic permanent magnet materials include anisotropic powder materials and anisotropic bulk materials, among which anisotropic powder materials can be oriented and aligned in adhesives under the action of magnetic field force or mechanical force to produce anisotropic adhesive bulk materials. In addition to being produced directly using anisotropic powder materials, anisotropic bulk materials can also be produced using isotropic powder materials through a thermal deformation processing process to produce RE2Fe 14 Anisotropy can be obtained by dissolving and precipitating B crystal grains and allowing them to grow preferentially to form an oriented texture. As can be seen from the above, the degree of orientation in anisotropic permanent magnet materials is an important factor in determining the magnetic properties of the material.
[0005] A Chinese patent application bearing application number 200610147137.5 provides a method for producing nanocrystalline anisotropic rare earth permanent magnet magnetic powder, in which the quenched magnetic powder is subjected to hot rolling treatment, so that the quenched magnetic powder undergoes plastic deformation and forms an oriented texture; the hot rolling action time is short, and the orientation degree of the magnetic powder is low, so two hot rolling processes are required to improve the orientation degree; however, repeated hot rolling inevitably generates a large amount of residual stress in the powder, so that the coercive force of the produced magnetic powder is low (10.7 kOe), and there is room for improving the magnetic properties (Patent Document 1). A Chinese patent application with application number 201110428088.3 provides an anisotropic nanocrystalline composite permanent magnet material and a manufacturing method thereof, which comprises preparing nanocrystalline magnetic powder by quenching or mechanical alloying, preparing an anisotropic magnet by hot pressing thermal deformation, crushing, and then removing the rare earth-rich phase on the surface of the magnet by acid etching to obtain anisotropic sheet crystals, and then coating or covering the surface of the anisotropic sheet crystals with a soft magnetic phase to obtain nanocomposite sheet crystal grains, and manufacturing the nanocomposite sheet crystal grains into a full-density anisotropic nanocrystalline composite magnetic material by hot pressing method, and the magnetic energy product can reach 42 MGOe or more. However, the manufacturing process is complicated, the production cycle is long, the process is difficult to control, and the production efficiency is low, which is not conducive to large-scale industrialization (Patent Document 2).
[0006] Therefore, there is an urgent need to develop a method for producing anisotropic rare earth permanent magnet materials that improves the magnetic properties of the anisotropic rare earth permanent magnet materials, simplifies the process, and improves production efficiency. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] China Patent Application Publication No. 101174499 [Patent Document 2] China Patent Application Publication No. 102436887 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material and a rare earth permanent magnet material, which improve the magnetic properties of the anisotropic rare earth permanent magnet material, simplify the process, and improve production efficiency. [Means for solving the problem]
[0009] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Preparing a rare earth permanent magnet raw material magnetic powder at a temperature of 710°C to 740°C for 5 to 120 minutes under vacuum or protective atmosphere to prepare a precursor sheet-shaped nanocrystalline magnetic powder; S2. Thermal deformation processing orientation treatment: At a temperature of 500 to 850 ° C, the precursor sheet-shaped nanocrystalline magnetic powder or the sealing body or base material manufactured from the precursor sheet-shaped nanocrystalline magnetic powder is subjected to thermal deformation processing to regularly arrange the sheet-shaped nanocrystals and manufacture an oriented sheet-shaped nanocrystalline rare earth permanent magnet material; S3. Orientation optimization post-treatment: The oriented sheet-shaped nanocrystalline rare earth permanent magnet material is kept at a temperature of 600 to 850 ° C for 3 to 120 minutes in a vacuum or protective atmosphere to produce an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material; Here, the raw material magnetic powder for the rare earth permanent magnet is a nanocrystalline magnetic powder or an amorphous magnetic powder, the average particle size of the nanocrystalline magnetic powder is 200 nm or less, the number of crystal grains of the sheet-shaped nanocrystals inside the produced precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the average particle size in the thickness direction of the crystal grains of the sheet-shaped nanocrystals is 10 to 300 nm, and the average particle size in the length direction of the crystal grains of the sheet-shaped nanocrystals is 30 to 800 nm.
[0010] Optionally, the rare earth permanent magnet raw magnetic powder comprises RE x Fe 100-x-y-z TM y B zRE is one or more of La, Ce, Pr, Nd, Y, Dy, and Tb, TM is one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al, and Zn, and x, y, and z represent mass fractions of the elements, where 26.0≦x≦36.0, 0.14≦y≦8.0, and 0.8≦z≦1.36.
[0011] Optionally, the process of S1. producing precursor sheet-shaped nanocrystalline magnetic powder is to keep the rare earth permanent magnet raw material magnetic powder at a temperature of 710°C to 740°C for 5 to 100 minutes under vacuum or protective atmosphere to produce the precursor sheet-shaped nanocrystalline magnetic powder, wherein the number of crystal grains of the sheet-shaped nanocrystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the average grain size in the thickness direction of the crystal grains of the sheet-shaped nanocrystals is 50 to 150 nm, and the average grain size in the length direction of the crystal grains of the sheet-shaped nanocrystals is 150 to 600 nm.
[0012] Optionally, the process of S1. producing precursor sheet-shaped nanocrystalline magnetic powder is to keep the rare earth permanent magnet raw material magnetic powder at a temperature of 710°C to 740°C for 15 to 60 minutes under vacuum or protective atmosphere to produce the precursor sheet-shaped nanocrystalline magnetic powder, wherein the number of crystal grains of the sheet-shaped nanocrystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the average grain size in the thickness direction of the crystal grains of the sheet-shaped nanocrystals is 60 to 100 nm, and the average grain size in the length direction of the crystal grains of the sheet-shaped nanocrystals is 180 to 400 nm.
[0013] Optionally, the process of the hot deformation in S2. hot deformation orientation treatment is one or more of hot rolling deformation, hot pressing deformation and hot extrusion deformation.
[0014] Optionally, the hot rolling deformation process is to carry out hot rolling deformation on the precursor sheet-shaped nanocrystalline magnetic powder under vacuum or protective atmosphere to arrange the sheet-shaped nanocrystals regularly, the hot rolling deformation temperature is 600-850°C, and the deformation amount of the precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction is 50-90%.
[0015] Optionally, the hot press deformation process includes vacuum sealing the precursor sheet-shaped nanocrystalline magnetic powder with a sealing material to obtain a sealed body, and then performing hot press deformation on the sealed body at a temperature of 600 to 850°C to arrange the sheet-shaped nanocrystals regularly, the hot press deformation speed is 0.02 to 3 mm / s, and the deformation amount of the sealed body in the hot press direction is 50 to 90%.
[0016] Optionally, the hot press deformation process is to manufacture the precursor sheet-shaped nanocrystalline magnetic powder into a green body having a density of 65.0% to 99.9% at room temperature to 800°C, and then perform hot press deformation on the green body to arrange the sheet-shaped nanocrystals regularly, wherein the temperature of the hot press deformation is 600 to 850°C, the deformation amount of the green body in the hot press direction is 50 to 90%, and the speed of the hot press deformation is 0.02 to 3 mm / s.
[0017] Optionally, the hot extrusion deformation process is to prepare the precursor sheet-shaped nanocrystalline magnetic powder into a green body having a density of 65.0% to 99.9% at room temperature to 800°C, and then perform hot extrusion deformation on the green body to arrange the sheet-shaped nanocrystals regularly, wherein the temperature of the hot extrusion deformation is 600 to 850°C, and the speed of the hot extrusion deformation is 0.02 to 3 mm / s.
[0018] In a second aspect, the present invention provides an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material obtained by the above-mentioned method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material. Effect of the Invention
[0019] In summary, the present invention has at least one of the following beneficial effects:
[0020] 1. The manufacturing method of an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material provided by the present invention is as follows: S1. A precursor sheet-shaped nanocrystalline magnetic powder is obtained by manufacturing a precursor sheet-shaped nanocrystalline magnetic powder, and the number of crystal grains of the sheet-shaped nanocrystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the crystal grains of the sheet-shaped nanocrystals have an average grain size in the thickness direction of 10-300 nm and an average grain size in the length direction of the crystal grains of the sheet-shaped nanocrystals are 30-800 nm, and in the subsequent thermal deformation processing process, the sheet-shaped nanocrystals of the precursor sheet-shaped nanocrystalline magnetic powder have a specific structure and have shape anisotropy, so that they are easily rotated under the action of a stress field, and the thickness of the sheet-shaped nanocrystals is driven to be regularly arranged along the thermal deformation direction, forming an oriented aggregate structure, improving the degree of orientation, and manufacturing an anisotropic rare earth permanent magnet material with high performance; B r is 14.1kGs or more, H cj is 13.2kOe or more, (BH) max can reach 45.7 MGOe or more, and more preferably, B r is 14.2kGs or more, H cj is 13.8kOe or more, (BH) max can reach 47.1 MGOe or more, and most preferably, B r is 14.4kGs, (BH) max can reach 48.1 MGOe.
[0021] 2. The manufacturing method of anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material provided by the present invention is such that the sheet-shaped nanocrystals of the precursor sheet-shaped nanocrystalline magnetic powder can be easily rotated and oriented. On the one hand, in the S2. thermal deformation processing orientation process, a normal low-speed deformation process such as a thermal deformation speed of 0.1 mm / s is used, and a high degree of orientation can be obtained, resulting in higher remanence and magnetic energy product; on the other hand, unlike equiaxed crystals or amorphous crystals that can be oriented through dissolution and precipitation in the thermal deformation processing process, the sheet-shaped nanocrystals can be easily rotated and oriented, so that an excellent oriented texture can be obtained within a very short thermal deformation time, thereby improving the production efficiency of anisotropic rare earth permanent magnet material. When the thermal deformation speed is 0.8 mm / s or more, high magnetic properties can still be obtained.
[0022] 3. The manufacturing method of the anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material provided by the present invention uses specific S1. manufacturing precursor sheet-shaped nanocrystalline magnetic powder, S2. hot deformation processing orientation treatment, and S3. orientation optimization post-treatment, and the manufactured sheet-shaped nanocrystal undergoes hot deformation processing orientation, and finally optimizes the orientation, and the three steps act synergistically to jointly improve the magnetic properties of the anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material.
[0023] 4. The manufacturing method of the anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material provided by the present invention has a simple process, high controllability of the manufacturing process, and high production efficiency. The obtained anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material has excellent performance and is suitable for industrial mass production. [Brief description of the drawings]
[0024] [Figure 1] (a) is a scanning electron microscope image (SEM) of the nanocrystalline quenched magnetic powder of Example 1 of the present invention, (b) is a scanning electron microscope image of the precursor sheet-shaped nanocrystalline magnetic powder of Example 1 of the present invention, (c) is a scanning electron microscope image of the oriented sheet-shaped nanocrystalline magnetic powder of Example 1 of the present invention, and (d) is a scanning electron microscope image of the anisotropic sheet-shaped nanocrystalline magnetic powder of Example 1 of the present invention. [Diagram 2]2(a) is a scanning electron microscope image of the precursor sheet-shaped nanocrystalline magnetic powder of Example 1, (b) is an enlarged view of the R1 box selected area in (a) of Figure 2, (c) is a scanning electron microscope image of the precursor sheet-shaped nanocrystalline magnetic powder of Comparative Example 1, (d) is an enlarged view of the R2 box selected area in (c) of Figure 2, (e) is a scanning electron microscope image of the precursor sheet-shaped nanocrystalline magnetic powder of Comparative Example 2, and (f) is an enlarged view of the R3 box selected area in (e) of Figure 2. [Diagram 3] 1 shows X-ray diffraction patterns (XRD) of Example 1 and Comparative Examples 1 to 4. [Figure 4] (a) is a scanning electron microscope image (SEM) of the nanocrystalline quenched magnetic powder of Example 4 of the present invention, (b) is a scanning electron microscope image of the precursor sheet-shaped nanocrystalline magnetic powder of Example 4 of the present invention, (c) is a scanning electron microscope image of the oriented sheet-shaped nanocrystalline magnetic powder of Example 4 of the present invention, and (d) is a scanning electron microscope image of the anisotropic sheet-shaped nanocrystalline magnetic powder of Example 4 of the present invention. [Diagram 5] 1 shows X-ray diffraction patterns (XRD) of Example 4 and Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present invention provides a method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material and a rare earth permanent magnet material, and in order to make the objectives, technical solutions and effects of the present invention clearer, the present invention will be described in more detail below. It should be understood that the specific examples described herein are only for illustrating the present invention, and are not intended to limit the present invention.
[0026] RE2Fe in RE-Fe-B permanent magnet material 14The B phase has a tetragonal crystal structure and strong uniaxial anisotropy. Ideally, the magnetic properties of anisotropic permanent magnet materials are twice as high as those of isotropic permanent magnet materials. Dense anisotropic RE-Fe-B permanent magnets are classified into sintered magnets and heat-deformed magnets according to the manufacturing method. Compared with sintered magnets with micron crystal structures, heat-deformed magnets have unique nano-crystal structures and abundant grain boundary structures, and can obtain high magnetic properties without using medium or heavy rare earths, and are considered to be the rare earth permanent magnet material with the greatest development potential. The anisotropy of heat-deformed magnets is due to the effect of the RE2Fe under the action of temperature and stress fields. 14 The orientation texture is obtained after the formation of lamellar structure crystal grains regularly arranged along the thermal deformation direction. The formation of the orientation texture is mainly due to the action of temperature and stress fields in RE2Fe 14 The precursors used in conventional hot deformation processes are generally amorphous or equiaxed nanocrystalline magnetic powders, and these precursor powders are generally RE2Fe 14Because the B crystal grains need enough time to dissolve and precipitate and grow preferentially to form an oriented texture, the deformation speed of the normal process is very low, generally less than 0.2mm / s, which greatly limits the production efficiency of heat-deformed magnets. Regarding the production of anisotropic RE-Fe-B magnetic powder, the traditional manufacturing methods of anisotropic magnetic powder mainly include crushing method, HDDR method and mechanical ball milling method of anisotropic heat-deformed magnets, and these manufacturing methods are time-consuming, complex and cumbersome. In addition, the magnetic powders produced by these methods are basically in random form, and in the subsequent molding, an oriented magnetic field is required to obtain anisotropic bonded magnets, which greatly increases the manufacturing cost. Through long-term experimental research, the applicant has surprisingly found that a precursor sheet-shaped nanocrystalline magnetic powder with a specific structure can be obtained through a specific manufacturing process of nanocrystalline magnetic powder or amorphous magnetic powder, and the number of sheet-shaped nanocrystals inside the magnetic powder accounts for more than 85% of the total number of crystal grains. The sheet-shaped nanocrystals with a specific structure have shape anisotropy, so they rotate very easily under the action of the subsequent thermal deformation stress field, forming an oriented aggregate structure in which the thickness direction of the sheet-shaped nanocrystals is regularly arranged parallel to the thermal deformation direction, thereby improving the degree of orientation. By further combining with post-treatment of a specific process and optimizing the orientation, an anisotropic rare earth permanent magnet material with excellent magnetic properties is manufactured. The present invention is based on this research.
[0027] The component of the rare earth permanent magnet raw material magnetic powder used in this invention is RE x Fe 100-x-y-z TM y B zRE is one or more of La, Ce, Pr, Nd, Y, Dy and Tb, TM is one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al, Zn, and x, y, z represent the mass fractions of the elements, where 26.0≦x≦36.0, 0.14≦y≦8.0, 0.8≦z≦1.36. By using the rare earth permanent magnet raw material magnetic powder of the above composition, a rare earth permanent magnet material having excellent magnetic properties can be manufactured. The rare earth permanent magnet raw material magnetic powder used in the present invention is one or more of quenched magnetic powder, HDDR magnetic powder, ball milled magnetic powder, mechanically crushed magnetic powder, and mechanically alloyed magnetic powder.
[0028] The present invention provides a method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material, which includes the following steps:
[0029] S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: A rare earth permanent magnet raw material magnetic powder is kept at a temperature of 710°C to 740°C for 5 to 120 minutes under vacuum or protective atmosphere to prepare a precursor sheet-shaped nanocrystalline magnetic powder, in which the rare earth permanent magnet raw material magnetic powder is a nanocrystalline magnetic powder or an amorphous magnetic powder, the average particle size of the nanocrystalline magnetic powder is 200 nm or less, the number of crystal grains of the sheet-shaped nanocrystalline magnetic powder inside the prepared precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the average particle size of the crystal grains of the sheet-shaped nanocrystalline magnetic powder in the thickness direction is 10 to 300 nm, and the average particle size of the crystal grains of the sheet-shaped nanocrystalline magnetic powder in the length direction is 30 to 800 nm.
[0030] The nanocrystalline magnetic powder or amorphous magnetic powder is obtained by the above-mentioned specific manufacturing process, and the number of crystal grains of the sheet-shaped nanocrystalline magnetic powder precursor has a specific sheet-shaped nanocrystalline structure, and the number of crystal grains of the sheet-shaped nanocrystalline magnetic powder accounts for more than 85% of the total number of crystal grains, and the sheet-shaped nanocrystalline magnetic powder has shape anisotropy, so that it rotates very easily under the action of a stress field, and the thickness direction of the crystal grains is regularly arranged along the direction parallel to the thermal deformation, forming an oriented aggregate structure. On the one hand, the sheet-shaped nanocrystalline magnetic powder precursor can easily rotate and orient, and can produce an anisotropic permanent magnet material with excellent magnetic properties at a normal thermal deformation rate, and on the other hand, can produce an anisotropic permanent magnet material with still excellent magnetic properties at a high thermal deformation rate, which is helpful in improving production efficiency. Preferably, the temperature for producing the precursor sheet-shaped nanocrystalline magnetic powder is 710°C to 740°C, and the warming time is 5 to 100 min, and more preferably, the warming time is 15 to 60 min. Preferably, the average grain size in the thickness direction of the sheet-shaped nanocrystals in the precursor sheet-shaped nanocrystalline magnetic powder is 50 to 150 nm, and the average grain size in the length direction of the crystal grains is 150 to 600 nm, and more preferably, the average grain size in the thickness direction of the sheet-shaped nanocrystals is 60 to 100 nm, and the average grain size in the length direction of the crystal grains is 180 to 400 nm. Preferably, the number of the sheet-shaped nanocrystal grains in the precursor sheet-shaped nanocrystalline magnetic powder accounts for 90% or more of the total number of crystal grains, more preferably 94% or more, and even more preferably 98% or more.
[0031] S2. Thermal deformation orientation treatment: At a temperature of 500 to 850°C, the precursor sheet-shaped nanocrystalline magnetic powder or the sealed body or base material manufactured from the precursor sheet-shaped nanocrystalline magnetic powder is subjected to thermal deformation processing to regularly arrange the sheet-shaped nanocrystals and produce an oriented sheet-shaped nanocrystalline rare earth permanent magnet material.
[0032] Specifically, the process of the hot deformation processing in S2. hot deformation processing orientation treatment is one or more of hot rolling deformation, hot pressing deformation and hot extrusion deformation.
[0033] Here, the hot rolling deformation process is to carry out hot rolling deformation on the precursor sheet-shaped nanocrystalline magnetic powder under vacuum or protective atmosphere to arrange the sheet-shaped nanocrystals regularly, the hot rolling deformation temperature is 600-850°C, and the deformation amount of the precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction is 50-90%.Preferably, the hot rolling deformation temperature is 700-850°C, more preferably, the hot rolling deformation temperature is 750-850°C, and the deformation amount of the precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction is 60-80%.
[0034] Here, the process of hot press deformation is to vacuum seal the precursor sheet-shaped nanocrystalline magnetic powder with a sealing material to obtain a sealed body, and then perform hot press deformation on the sealed body at a temperature of 600 to 850 ° C to arrange the sheet-shaped nanocrystals regularly, the hot press deformation speed is 0.02 to 3.00 mm / s, and the deformation amount of the sealed body in the hot press direction is 50 to 90%. The sealing material is a plastic material, preferably a copper tube or a stainless steel tube. Preferably, the hot press deformation temperature is 700 to 850 ° C, more preferably, the hot press deformation temperature is 750 to 850 ° C, the deformation amount of the sealed body in the hot press direction is 60 to 80%, and the hot press deformation speed is 0.02 to 1.00 mm / s, 1.00 to 3.00 mm / s, more preferably, the hot press deformation speed is 0.02 to 0.2 mm / s, 0.2 to 3.00 mm / s.
[0035] Here, the hot press deformation process is to manufacture the precursor sheet-shaped nanocrystalline magnetic powder into a base material with a density of 65.0% to 99.9% at room temperature to 800 ° C, and perform hot press deformation on the base material to arrange the sheet-shaped nanocrystals regularly, the hot press deformation temperature is 600 to 850 ° C, the deformation amount of the base material in the hot press direction is 50 to 90%, and the hot press deformation speed is 0.02 to 3 mm / s. Preferably, the hot press deformation temperature is 700 to 850 ° C, more preferably, the hot press deformation temperature is 750 to 850 ° C, the deformation amount of the base material in the hot press direction is 60 to 80%, and the hot press deformation speed is 0.02 to 1.00 mm / s, 1.00 to 3.00 mm / s, more preferably, the hot press deformation speed is 0.02 to 0.2 mm / s, 0.2 to 3.00 mm / s.
[0036] S3. Orientation optimization post-treatment: The oriented sheet-shaped nanocrystalline rare earth permanent magnet material is kept at a temperature of 600-850°C for 3-120 minutes in a vacuum or protective atmosphere to produce anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material.
[0037] The specific orientation optimization post-treatment mentioned above is useful for further growth of oriented crystal grains, improves anisotropy, optimizes uniform distribution of rare earth rich phase at crystal grain boundaries, and helps to remove residual stress caused by thermal deformation processing, thereby further improving magnetic properties.Preferably, the temperature is 750-850°C, and the time is 5-60 min.
[0038] The present invention provides an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material obtained by the above-mentioned method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material. The rare earth permanent magnet material produced by the present invention includes powder material and bulk material. Among them, the powder material is a sheet-shaped magnetic powder, and the sheet-shaped magnetic powder has shape anisotropy and the magnetic properties of the sheet-shaped magnetic powder itself are anisotropic, so that the sheet-shaped magnetic powder can not only be oriented by a stress field, but also be oriented by a magnetic field, and can even be oriented by both a stress field and a magnetic field. When using the powder material to produce magnets, it can be adapted to various industrial scenes and has a wide range of application prospects. The bulk material has excellent magnetic properties, and can directly produce the corresponding device types according to various application needs, and also has a wide range of application prospects.
[0039] The anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material produced by the present invention has the thickness direction of the sheet-shaped nanocrystals inside the rare earth permanent magnet material regularly arranged parallel to the thermal deformation direction, and the easy magnetization direction of the nanocrystals is parallel to the thickness direction of the crystal grains, so that the sheet-shaped nanocrystalline rare earth material exhibits anisotropy. The anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material produced has an average grain size in the thickness direction of the sheet-shaped nanocrystals of 30 to 200 nm and an average grain size in the length direction of 150 to 800 nm, and has excellent magnetic properties. Preferably, the average grain size in the thickness direction of the sheet-shaped nanocrystals is 50 to 150 nm, and the average grain size in the length direction is 200 to 600 nm.
[0040] The present invention will now be further described with reference to specific examples.
[0041] Example 1 This embodiment provides a method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Nd 29.89 Fe 62.62 Co 5.93 Ga 0.64 B 0.92(wt.%), the alloy ingot was melt-quenched, the linear speed of the quenching roller was 25 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50-450 μm was obtained. The nanocrystalline quenched magnetic powder was equiaxed. As shown in Figure 1(a), the measurement statistics were carried out by Nano Measurer statistical software, and the average particle size of the equiaxed crystal was 50 nm. Then, the nanocrystalline quenched magnetic powder was quenched in a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 720°C for 15 minutes in a vacuum of 10 Pa. As shown in Figure 1 (b), the average grain size in the thickness direction of the crystal grains of the precursor sheet-shaped nanocrystalline magnetic powder was 71 nm, and the average grain size in the length direction was 245 nm. The number of crystal grains of the sheet-shaped nanocrystalline crystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 98.1% of the total number of crystal grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Hot deformation orientation treatment: Using a two-roll mill, the precursor sheet-shaped nanocrystalline magnetic powder produced in S1 was subjected to hot rolling deformation treatment. Under an argon protective atmosphere, the hot rolling temperature was 780°C, and the deformation amount in the thickness direction of the magnetic powder after hot rolling was 65%. As shown in (c) of Figure 1, the sheet-shaped nanocrystals inside the magnetic powder after hot rolling were regularly arranged, and the thickness direction of the sheet-shaped nanocrystals was aligned parallel to the hot rolling deformation direction, producing an oriented sheet-shaped nanocrystalline magnetic powder. S3. Orientation optimization post-treatment: The aligned sheet-shaped nanocrystalline magnetic powder produced in S2 is placed in a vacuum chamber with a degree of vacuum of 1×10 -2 After heating at 800°C for 5 min under vacuum conditions of 10 Pa, the oriented crystal grains further grew, improving the anisotropy, optimizing the uniform distribution of the rare earth-rich phase at the crystal grain boundaries, and helping to remove residual stress, as shown in Figure 1(d). Anisotropic sheet-shaped nanocrystalline magnetic powder was produced, with the sheet-shaped nanocrystals having an average grain size in the thickness direction of 90 nm and an average grain size in the length direction of 305 nm.
[0042] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S1 of manufacturing the precursor sheet-shaped nanocrystalline magnetic powder in Example 1, the nanocrystalline quenched magnetic powder is kept in a vacuum at 720°C for 15 minutes, but is kept at 700°C for 20 minutes; all other manufacturing steps are the same as those in Example 1.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S1 of manufacturing the precursor sheet-shaped nanocrystalline magnetic powder in Example 1, the nanocrystalline quenched magnetic powder is kept in a vacuum at 720°C for 15 minutes, but is kept at 750°C for 30 minutes; all other manufacturing steps are the same as those in Example 1. FIG. 2 is a micro-morphology diagram of the magnetic powders produced from the S1. precursor sheet-shaped nanocrystalline magnetic powders of Example 1 and Comparative Examples 1 and 2. As can be seen from FIG. 2, the heating temperature produced from the S1. precursor sheet-shaped nanocrystalline magnetic powder in Comparative Example 1 is too low (700°C), so the growth of crystal grains is inhibited, and some of the crystal grains in the central region of the magnetic powder are still equiaxed crystals. The number of crystal grains of the sheet-shaped nanocrystals inside the magnetic powder accounts for 50.5% of the total number of crystal grains, which is much lower than the proportion of the sheet-shaped nanocrystals in Example 1. Furthermore, the average grain size in the thickness direction of the sheet-shaped nanocrystals inside the magnetic powder of Comparative Example 1 is 49 nm, and the average grain size in the length direction is 110 nm, which is smaller than the grain size of the sheet-shaped nanocrystals in Example 1, and the ratio of the grain size in the length direction to the grain size in the thickness direction is smaller than that of Example 1, and the shape anisotropy is inferior to that of Example 1. In Comparative Example 2, the heating temperature produced by S1. precursor sheet-shaped nanocrystalline magnetic powder was too high (750°C). Under such high temperature, the crystal grains on the roll surface of the magnetic powder grew abnormally very easily to form coarse crystals, the average grain size of the coarse crystals was 1.6 μm, and the proportion of abnormally grown coarse crystals reached 22.1% (the ratio of the thickness of the coarse crystal region to the total thickness of the magnetic powder), and sheet-shaped nanocrystals grew inside the magnetic powder, with the average grain size of the sheet-shaped nanocrystals in the thickness direction being 95 nm and the average grain size in the length direction being 320 nm.
[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step S1 of Example 1, the step of keeping the nanocrystalline quenched magnetic powder in a vacuum at 720°C for 15 minutes is omitted in the manufacturing step of the precursor sheet-shaped nanocrystalline magnetic powder; the other manufacturing steps are the same as those of Example 1.
[0045] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the deformation amount of the magnetic powder in the thickness direction after hot rolling of 65% in the S2. hot deformation processing orientation treatment step in Example 1 is replaced with the deformation amount of the magnetic powder in the thickness direction after hot rolling of 30%; the other manufacturing steps are the same as those of Example 1. The characteristics of the anisotropic magnetic powders produced in Example 1 and Comparative Examples 1 to 4 were measured using a vibrating sample magnetometer (VSM). Table 1. Magnetic properties of anisotropic magnetic powder JPEG2024546159000002.jpg76170The anisotropic magnetic powders produced in Example 1 and Comparative Examples 1 to 4 were mixed with 1 wt% epoxy resin, and then press-molded at room temperature under the action of an aligning magnetic field of 3 T to produce anisotropic bonded magnets with a diameter of φ10 mm. The density of the bonded magnets was 5.9 g / cm. 3 The XRD patterns of the bonded magnets were measured, and the degree of orientation of the anisotropic magnetic powders produced in Example 1 and Comparative Examples 1 to 4 was characterized by the ratio of the diffraction peak intensities of (006) and (105) on the orientation plane of the anisotropic bonded magnet, as shown in FIG. 3. Referring to Table 1 and FIG. 3, it can be seen that the degree of orientation and magnetic properties of the anisotropic sheet-shaped nanocrystalline magnetic powder of Example 1 are clearly superior to those of Comparative Examples 1 to 4. The main reason for this is that the precursor sheet-shaped nanocrystalline magnetic powder obtained by the quenched nanocrystalline magnetic powder of Example 1, S1. Production of precursor sheet-shaped nanocrystalline magnetic powder, has a high proportion of crystal grains of sheet-shaped nanocrystals inside, a large ratio of the length of the crystal grains of the sheet-shaped nanocrystals to the dimension in the thickness direction, and has excellent shape anisotropy. Therefore, the sheet-shaped nanocrystals easily rotate under the action of stress during the subsequent thermal deformation processing process, and the thickness direction of the sheet-shaped nanocrystals is regularly arranged along the thermal deformation direction (the direction of the arrow in FIG. 1(c)), resulting in an excellent oriented aggregate structure with a good degree of orientation. In Comparative Example 1, the proportion of sheet-shaped nanocrystals is significantly lower than that in Example 1. Therefore, the equiaxed crystals that do not form sheet-shaped nanocrystals need to undergo the process of dissolution, precipitation and orientation during the hot deformation process. As a result, the orientation time of the crystal grains is long and they cannot be sufficiently oriented during the hot rolling deformation process. As a result, the orientation degree of the produced magnetic powder is significantly lower than that of Example 1. The orientation degree is an important factor that affects the remanence. Correspondingly, the remanence and magnetic energy product of Comparative Example 1 are significantly lower than those of Example 1. In Comparative Example 2, the magnetic powder forms a large amount of coarse crystals through the production step of S1. precursor sheet-shaped nanocrystalline magnetic powder, which inhibits the dissolution, precipitation and orientation of crystal grains in the subsequent hot deformation processing process. As a result, the orientation degree of Comparative Example 2 is significantly lower than that of Example 1. Correspondingly, the residual magnetism of Comparative Example 2 is significantly lower than that of Example 1. At the same time, due to the influence of the coarse crystals, the coercive force of Comparative Example 2 is significantly reduced, and the magnetic energy product of Comparative Example 2 is significantly lower than that of Example 1. In Comparative Example 3, the quenched nanocrystalline magnetic powder was not heated and kept at a constant temperature, so the crystal grains remained as fine equiaxed crystals, which helped the crystal grains to dissolve and precipitate in the subsequent thermal deformation process to form fine crystal grains. The coercive force was higher than that of Example 1, but the equiaxed crystals were unable to complete sufficient orientation during the thermal deformation process, so the degree of orientation of Comparative Example 3 was significantly lower than that of Example 1, and correspondingly, the remanence and magnetic energy product were also significantly lower than those of Example 1. In Comparative Example 4, the deformation amount during the thermal deformation processing of the magnetic powder obtained by the production of S1. precursor sheet-shaped nanocrystalline magnetic powder is significantly lower than that of Example 1, and the orientation of the sheet-shaped nanocrystals during the thermal deformation processing is insufficient, so the orientation degree of Comparative Example 4 is significantly lower than that of Example 1, and the residual magnetism and magnetic energy product are significantly lower than those of Example 1.
[0046] Example 2 This embodiment provides a method for producing anisotropic nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Pr 2.1 Nd 27.85 Fe 62.56 Co 5.93 Ga 0.64B 0.92 (wt.%), the linear speed of the quenching roller was 35 m / s, and amorphous quenched magnetic powder with a particle size of 50 to 450 μm was obtained. The amorphous quenched magnetic powder was then cooled to a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 730°C for 20 minutes in a vacuum of 1 Pa. Measurement statistics were performed using Nano Measurer statistical software. The average grain size in the thickness direction of the crystal grains of the obtained precursor sheet-shaped nanocrystalline magnetic powder was 90 nm, the average grain size in the length direction was 200 nm, and the number of crystal grains of the sheet-shaped nanocrystalline crystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 91.5% of the total number of crystal grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Hot deformation orientation treatment: Using a two-roll mill, the precursor sheet-shaped nanocrystalline magnetic powder produced in S1 was subjected to hot rolling deformation treatment. Under an argon protective atmosphere, the hot rolling temperature was 780°C, and the deformation amount in the thickness direction of the magnetic powder after hot rolling was 60%. After hot rolling, the sheet-shaped nanocrystals inside the magnetic powder were regularly arranged, and the thickness direction of the sheet-shaped nanocrystals was aligned parallel to the thermal deformation direction of the magnetic powder, producing an oriented sheet-shaped nanocrystalline magnetic powder. S3. Orientation optimization post-treatment: The aligned sheet-shaped nanocrystalline magnetic powder produced in S2 is placed in a vacuum chamber with a degree of vacuum of 1×10 -2 Under vacuum conditions of 10 Pa, the material was kept at 800°C for 7 min, which was conducive to further growth of oriented crystal grains, improved anisotropy, optimized the uniform distribution of rare earth-rich phase at the crystal grain boundaries, and removed residual stress, producing anisotropic sheet-shaped nanocrystalline magnetic powder. The average grain size of the sheet-shaped nanocrystals in the thickness direction was 103 nm, and the average grain size in the length direction was 275 nm.
[0047] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that in step S1 of the production step of the precursor sheet-shaped nanocrystalline magnetic powder in Example 2, the step of keeping the amorphous quenched magnetic powder at 730°C in a vacuum for 20 minutes is omitted; the other production steps are the same as those in Example 2. The characteristics of the anisotropic magnetic powders produced in Example 2 and Comparative Example 5 were measured using a vibrating sample magnetometer (VSM). The measurement results are shown in Table 2. Table 2. Magnetic properties of anisotropic magnetic powder JPEG2024546159000003.jpg40170 The anisotropic magnetic powder produced in Example 2 was used to produce an anisotropic bonded magnet under the same process conditions as in Example 1. e14 Diffraction peak I of phase B (006) / I (105) = 0.75 was measured, which indicates that the sheet-shaped nanocrystals of the anisotropic magnetic powder prepared in Example 2 have regular orientation. Referring to Table 2, it can be seen that the magnetic properties of the anisotropic sheet-shaped nanocrystal magnetic powder of Example 2 are obviously superior to those of Comparative Example 5, the main reason being that the quenched nanocrystal magnetic powder of Example 2 is S1. The precursor sheet-shaped nanocrystal magnetic powder obtained by the preparation of the precursor sheet-shaped nanocrystal magnetic powder has a high proportion of crystal grains of the inner sheet-shaped nanocrystals, and the crystal grains can be fully oriented, while the amorphous quenched magnetic powder of Comparative Example 5 is directly subjected to hot deformation processing, and the amorphous structure first nucleates and then forms a structure during the hot deformation processing, so it requires a sufficient time, and as can be seen from the magnetic properties of Comparative Example 5, the amorphous quenched magnetic powder cannot directly obtain an oriented texture by hot rolling deformation, and shows isotropic characteristics.
[0048] Example 3 This embodiment provides a method for producing anisotropic nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Nd 29.39 Ce 0.5 Fe 62.76 Co 5.93 Ga 0.5 B 0.92(wt.%) was mechanically crushed to make the particle size of the crushed magnetic powder less than 1 mm, and then the crushed magnetic powder was processed by planetary ball milling at room temperature, using a stainless steel ball milling tank under argon protection, the ball milling rotation speed was 400 r / min, the ball material ratio was 10:1, and the ball milling time was 6 h, to produce ball-milled nanocrystalline magnetic powder with an average particle size of 30 nm, and the ball-milled nanocrystalline magnetic powder was milled in a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 710°C for 30 minutes in a vacuum of 1 Pa. Measurement statistics were performed using Nano Measurer statistical software. The average grain size in the thickness direction of the crystal grains of the obtained precursor sheet-shaped nanocrystalline magnetic powder was 75 nm, the average grain size in the length direction was 240 nm, and the number of crystal grains of the sheet-shaped nanocrystalline crystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 92.5% of the total number of crystal grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Hot deformation orientation treatment: Using a two-roll mill, the precursor sheet-shaped nanocrystalline magnetic powder produced in S1 was subjected to hot rolling deformation treatment. Under an argon protective atmosphere, the hot rolling temperature was 800°C, and the deformation amount in the thickness direction of the magnetic powder after hot rolling was 65%. After hot rolling, the sheet-shaped nanocrystals inside the magnetic powder were regularly arranged, and the thickness direction of the sheet-shaped nanocrystals was aligned parallel to the thermal deformation direction, producing an oriented sheet-shaped nanocrystalline magnetic powder. S3. Orientation optimization post-treatment: The aligned sheet-shaped nanocrystalline magnetic powder produced in S2 is placed in a vacuum chamber with a degree of vacuum of 1×10 -2 Under vacuum conditions of 10 Pa, the temperature was kept at 820°C for 10 min, which was conducive to further growth of oriented crystal grains, improved anisotropy, and optimized the uniform distribution of rare earth-rich phase at the crystal grain boundaries, producing anisotropic sheet-shaped nanocrystalline magnetic powder. The average grain size of the sheet-shaped nanocrystals in the thickness direction was 91 nm, and the average grain size in the length direction was 295 nm.
[0049] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that in step S1 of Example 3, the step of heating the ball-milled nanocrystalline magnetic powder in a vacuum at 710°C for 30 minutes is omitted; the other manufacturing steps are the same as those of Example 3. The characteristics of the anisotropic magnetic powders produced in Example 3 and Comparative Example 6 were measured using a vibrating sample magnetometer (VSM), and the measurement results are shown in Table 3. Table 3. Magnetic properties of anisotropic magnetic powder The anisotropic magnetic powders produced in Example 3 and Comparative Example 6 were used to produce anisotropic bonded magnets under the same process conditions as in Example 1. The Nd2Fe 14 Diffraction peak I of phase B (006) / I (105) = 0.77, Nd2Fe in Comparative Example 6 14 Diffraction peak I of phase B (006) / I (105) = 0.75, which indicates that the sheet-shaped nanocrystals of the anisotropic magnetic powder produced in Example 3 have regular orientation and are superior to the orientation degree of Comparative Example 6. Referring to Table 3, it can be seen that the magnetic properties of the anisotropic sheet-shaped nanocrystal magnetic powder of Example 3 are obviously superior to those of Comparative Example 6, and the main reason for this is that the ball-milled nanocrystal magnetic powder of Example 3, which is obtained by the preparation of S1. precursor sheet-shaped nanocrystal magnetic powder, has a high ratio of the number of crystal grains of the inner sheet-shaped nanocrystals, which is helpful for the orientation of the crystal grains of the anisotropic magnetic powder. During the ball milling process, the ball milling is performed using a stainless steel ball milling tank, and α-Fe impurities are inevitably mixed in, so the magnetic properties of the anisotropic sheet-shaped nanocrystal magnetic powder of Example 3 are lower than those of the anisotropic sheet-shaped nanocrystal magnetic powder of Example 1.
[0050] Example 4 This embodiment provides a method for producing anisotropic nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Nd 29.89 Fe 62.62 Co 5.93 Ga0.64 B 0.92 (wt.%) alloy ingot was melt-quenched, the linear speed of the quenching roller was 25 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50-450 μm was obtained. The nanocrystalline quenched magnetic powder was equiaxed. As shown in Figure 4(a), the measurement statistics were carried out by Nano Measurer statistical software, and the average particle size of the equiaxed grains was 50 nm. Then, the nanocrystalline quenched magnetic powder was quenched in a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 730°C for 30 minutes in a vacuum of 10 Pa. As shown in Figure 4 (b), the average grain size in the thickness direction of the crystal grains of the precursor sheet-shaped nanocrystalline magnetic powder was 85 nm, and the average grain size in the length direction was 280 nm. The number of sheet-shaped nanocrystalline grains inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 98.5% of the total number of grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Thermal deformation processing orientation treatment: Using a vacuum induction hot press sintering furnace, hot press-thermal deformation is performed on the precursor sheet-shaped nanocrystalline magnetic powder produced in S1., and the vacuum degree is 1×10 -2 The hot pressing temperature was 780°C, the hot pressing pressure was 200MPa, and the heat retention time was 1min to produce a hot pressed green body with a density of 99%. The hot pressed green body was then subjected to subsequent hot deformation to obtain a hot deformed magnet. The hot deformation temperature was 780°C, the hot deformation speed was 0.86mm / s, and the deformation amount in the height direction was 70%. As shown in (c) of Figure 4, the sheet-shaped nanocrystals inside the hot deformed magnet were regularly arranged, and the thickness direction of the sheet-shaped nanocrystals was aligned parallel to the direction of hot deformation, producing an oriented sheet-shaped nanocrystal magnet. S3. Post-treatment for optimizing orientation: The aligned sheet-shaped nanocrystal magnets produced in S2 are placed in a vacuum chamber with a degree of vacuum of 1×10 -2The magnet was then heated at 800°C for 5 min under vacuum conditions of 10 Pa, which helped to further grow the oriented crystal grains, improve the anisotropy, and optimize the uniform distribution of the rare earth-rich phase at the grain boundaries, as shown in Figure 4(d), and helped to remove residual stress. The average grain size of the sheet nanocrystals in the thickness direction of the produced anisotropic sheet nanocrystal magnet was 98 nm, and the average grain size in the length direction was 320 nm.
[0051] Comparative Example 7 The difference between Comparative Example 7 and Example 4 is that in step S1 of the production step of the precursor sheet-shaped nanocrystalline magnetic powder in Example 4, the step of keeping the nanocrystalline quenched magnetic powder at 730°C in a vacuum for 30 minutes is omitted; the other production steps are the same as those in Example 4. The characteristics of the anisotropic magnets produced in Example 4 and Comparative Example 7 were measured using a vibrating sample magnetometer (VSM). The measurement results are shown in Table 4. Table 4. Magnetic properties of anisotropic magnets FIG. 4 shows XRD patterns of the anisotropic magnets of Example 4 and Comparative Example 7. 14 Diffraction peak I of phase B (006) / I (105) = 1.12, Nd2Fe in Comparative Example 7 14 Diffraction peak I of phase B (006) / I (105) = 0.97, which indicates that the sheet-shaped nanocrystals of the anisotropic magnet produced in Example 4 have a regular orientation, and the degree of orientation is superior to that of Comparative Example 7. Referring to Table 4, it can be seen that the magnetic properties of each anisotropic sheet-shaped nanocrystal magnet of Example 4 are clearly superior to Comparative Example 7, and the main reason for this is that the precursor sheet-shaped nanocrystal magnetic powder obtained by the production of S1. precursor sheet-shaped nanocrystal magnetic powder of Example 4 has a high ratio of crystal grains of the internal sheet-shaped nanocrystals, which helps to orient the crystal grains of the anisotropic magnet, and the sheet-shaped nanocrystals rotate and orient in the stress field, so that the anisotropic magnet can still obtain an excellent oriented texture under high-speed deformation conditions of 0.86 mm / s.
[0052] Example 5 The difference between Example 5 and Example 4 is that the thermal deformation rate in Example 5 in step S2. Thermal deformation processing orientation treatment step of Example 4 is 0.1 mm / s instead of 0.86 mm / s, and the other manufacturing steps are the same as those of Example 4. The anisotropic magnet produced in Example 5 had a sheet-shaped nanocrystal with an average grain size in the thickness direction of 101 nm and an average grain size in the length direction of 330 nm.
[0053] Comparative Example 8 The difference between Comparative Example 8 and Example 5 is that Comparative Example 8 omits the step of keeping the nanocrystalline quenched magnetic powder at 730°C in a vacuum for 30 minutes in step S1 of the production step of the precursor sheet-shaped nanocrystalline magnetic powder in Example 5; the other production steps are the same as those of Example 5. The characteristics of the anisotropic magnets produced in Example 5 and Comparative Example 8 were measured using a vibrating sample magnetometer (VSM). The measurement results are shown in Table 5. Table 5. Magnetic properties of anisotropic magnets JPEG2024546159000006.jpg40170 Using the same measurement method as in Example 4, the Nd2Fe 14 Diffraction peak I of phase B (006) / I (105) = 1.21, Nd2Fe in Comparative Example 8 14 Diffraction peak I of phase B (006) / I (105) = 1.05, which indicates that the sheet-shaped nanocrystals of the anisotropic magnetic powder produced in Example 5 have regular orientation and are superior to the orientation degree of Comparative Example 8. Referring to Table 5, it can be seen that the magnetic properties of the anisotropic sheet-shaped nanocrystal magnetic powder of Example 5 are obviously superior to Comparative Example 8, and the main reason for this is that the precursor sheet-shaped nanocrystal magnetic powder obtained by the quenched nanocrystal magnetic powder production of S1. precursor sheet-shaped nanocrystal magnetic powder has a high ratio of the number of crystal grains of the inner sheet-shaped nanocrystals, which is helpful for the orientation of the crystal grains of the anisotropic magnetic powder. Referring to Examples 4 and 5, Example 5 has a slower deformation speed, which is more helpful for the rotation and orientation of the sheet-shaped nanocrystals during the thermal deformation process, and a better oriented texture was obtained.
[0054] Example 6 This embodiment provides a method for producing anisotropic nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Nd 29.89 Fe 62.52 Co 5.93 Ga 0.64 Nb 0.1 B 0.92 (wt.%), the linear speed of the quenching roller is 25 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm is obtained. The nanocrystalline quenched magnetic powder is equiaxed and has an average particle size of 50 nm. The nanocrystalline quenched magnetic powder is then cooled to a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 740°C for 60 minutes in a vacuum of 10 Pa. The average grain size of the crystal grains in the obtained precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction was 92 nm, and the average grain size in the length direction was 270 nm. The number of crystal grains of the sheet-shaped nanocrystalline magnetic powder inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 94.7% of the total number of crystal grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Thermal deformation processing orientation treatment: The precursor sheet-shaped nanocrystalline magnetic powder produced in S1 is vacuum sealed with a copper tube. The inner diameter of the copper tube is 15 mm, the wall thickness is 2 mm, and the vacuum degree of the vacuum sealing is 1×10 -2 The strain rate was 780°C, the strain rate was 0.80 mm / s, and the deformation amount of the encapsulated body in the height direction was 90%, resulting in the production of an oriented sheet-shaped nanocrystalline magnet. S3. Post-treatment for alignment optimization: Remove the copper tube from the aligned nanocrystalline magnet sheet produced in S2. and place in a vacuum chamber at 1×10. -2Under vacuum conditions of 10 Pa, the magnet was kept at 800°C for 10 min, which was conducive to further growth of oriented crystal grains, improved anisotropy, optimized the uniform distribution of rare earth-rich phase at the grain boundaries, and removed residual stress, resulting in the production of anisotropic sheet nanocrystal magnets. The average grain size of the sheet nanocrystals in the thickness direction was 103 nm, and the average grain size in the length direction was 295 nm.
[0055] Comparative Example 9 The difference between Comparative Example 9 and Example 6 is that in step S1 of the production step of the precursor sheet-shaped nanocrystalline magnetic powder in Example 6, the step of keeping the nanocrystalline quenched magnetic powder at 740°C in a vacuum for 60 minutes is omitted; the other production steps are the same as those in Example 6. The characteristics of the anisotropic magnets produced in Example 6 and Comparative Example 9 were measured using a vibrating sample magnetometer (VSM). The measurement results are shown in Table 6. Table 6. Magnetic properties of anisotropic magnets JPEG2024546159000007.jpg41170 Using the same measurement method as in Example 4, the Nd2Fe 14 Diffraction peak I of phase B (006) / I (105) = 1.08, Nd2Fe in Comparative Example 9 14 Diffraction peak I of phase B (006) / I (105) = 1.02, which indicates that the sheet-shaped nanocrystals of the anisotropic magnet produced in Example 6 have a regular orientation, which is superior to the orientation of Comparative Example 9. Referring to Table 6, it can be seen that the magnetic properties of each anisotropic sheet-shaped nanocrystal magnet of Example 6 are significantly superior to Comparative Example 9, and the main reason for this is that the precursor sheet-shaped nanocrystal magnetic powder obtained by the production of S1. precursor sheet-shaped nanocrystal magnetic powder of Example 6 has a high ratio of crystal grains of the internal sheet-shaped nanocrystals, which is helpful for the orientation of the crystal grains of the anisotropic magnet, and the sheet-shaped nanocrystals are rotated and oriented in the stress field, so that the anisotropic magnet can still obtain an excellent oriented texture under high-speed deformation conditions of 0.80 mm / s.
[0056] Example 7 This embodiment provides a method for producing anisotropic nanocrystalline rare earth permanent magnet material, which includes the following steps: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Nd 29.89 Fe 62.52 Co 5.93 Ga 0.64 Nb 0.1 B 0.92 (wt.%), the linear speed of the quenching roller is 25 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm is obtained. The nanocrystalline quenched magnetic powder is equiaxed and has an average particle size of 50 nm. The nanocrystalline quenched magnetic powder is then cooled to a vacuum of 5×10 -3 The precursor sheet-shaped nanocrystalline magnetic powder was produced by heating at 740°C for 60 minutes in a vacuum of 10 Pa. The average grain size of the crystal grains in the obtained precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction was 92 nm, the average grain size in the length direction was 270 nm, and the number of crystal grains of the sheet-shaped nanocrystalline crystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounted for 94.7% of the total number of crystal grains. At this time, the sheet-shaped nanocrystals were randomly arranged, and the easy magnetization direction of the sheet-shaped nanocrystals was parallel to the thickness direction of the sheet-shaped nanocrystals, so the precursor sheet-shaped nanocrystalline magnetic powder exhibited isotropy. S2. Hot deformation processing alignment treatment: The precursor sheet-shaped nanocrystalline magnetic powder produced in S1 is subjected to cold press densification treatment at room temperature, and the density of the obtained green body is 60%. Using a vacuum induction hot press sintering furnace, the sealed body is hot extruded, the hot extrusion temperature is 790°C, the hot extrusion speed is 0.70mm / s, and an aligned sheet-shaped nanocrystalline magnetic ring with an outer diameter of 30mm and a wall thickness of 1.5mm is produced. S3. Post-treatment for orientation optimization: The aligned sheet-shaped nanocrystalline magnetic ring produced in S2 is placed in a vacuum chamber with a degree of vacuum of 1×10 -2 Under vacuum conditions of 10 Pa, the heating at 800°C for 10 min was conducive to further growth of oriented crystal grains, improved anisotropy, optimized the uniform distribution of rare earth-rich phase at the crystal grain boundaries, and eliminated residual stress, resulting in the production of anisotropic sheet-shaped nanocrystal magnetic rings. The average grain size of the sheet-shaped nanocrystals in the thickness direction was 102 nm, and the average grain size in the length direction was 285 nm.
[0057] Comparative Example 10 The difference between Comparative Example 10 and Example 7 is that in step S1 of the production step of the precursor sheet-shaped nanocrystalline magnetic powder in Example 7, the step of keeping the nanocrystalline quenched magnetic powder in a vacuum at 740°C for 60 minutes is omitted; the other production steps are the same as those in Example 7. The characteristics of the anisotropic magnetic rings manufactured in Example 7 and Comparative Example 10 were measured using a vibrating sample magnetometer (VSM). The measurement results are shown in Table 7. Table 7. Magnetic properties of anisotropic magnetic rings JPEG2024546159000008.jpg38170 Using the same measurement method as in Example 4, the Nd2Fe 14 Diffraction peak I of phase B (006) / I (105) = 1.07, Nd2Fe of the oriented surface of Comparative Example 9 14 Diffraction peak I of phase B (006) / I (105) = 1.02, which indicates that the sheet-shaped nanocrystals of the anisotropic magnet produced in Example 7 have a regular orientation, and the degree of orientation is superior to that of Comparative Example 10. Referring to Table 7, it can be seen that the magnetic properties of each anisotropic sheet-shaped nanocrystal magnet of Example 7 are significantly superior to that of Comparative Example 10, and the main reason for this is that the precursor sheet-shaped nanocrystal magnetic powder obtained by the production of S1. precursor sheet-shaped nanocrystal magnetic powder of Example 7 has a high ratio of crystal grains of the internal sheet-shaped nanocrystals, which is helpful for the orientation of the crystal grains of the anisotropic magnet, and the sheet-shaped nanocrystals are easily rotated and oriented in the stress field, so that the anisotropic magnetic ring can still obtain an excellent oriented texture under the extrusion deformation condition of 0.70 mm / s.
[0058] It should be understood that the application of the present invention is not limited to the above examples, and those skilled in the art can make improvements or modifications based on the above description, and all these improvements and modifications should fall within the protection scope of the appended claims of the present invention.
Claims
1. A method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material, comprising the steps of: S1. Preparation of precursor sheet-shaped nanocrystalline magnetic powder: Rare earth permanent magnet raw material magnetic powder is kept at a temperature of 710°C to 740°C for 5 to 120 minutes under vacuum or protective atmosphere to prepare precursor sheet-shaped nanocrystalline magnetic powder; S2. Thermal deformation orientation treatment: at a temperature of 500 to 850°C, the precursor sheet-shaped nanocrystalline magnetic powder or the encapsulated body or base material made of the precursor sheet-shaped nanocrystalline magnetic powder is subjected to thermal deformation processing to regularly arrange the sheet-shaped nanocrystals and produce an oriented sheet-shaped nanocrystalline rare earth permanent magnet material; S3. Orientation optimization post-treatment: The oriented sheet-shaped nanocrystalline rare earth permanent magnet material is kept at a temperature of 600-850°C for 3-120 minutes under vacuum or protective atmosphere to produce anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material; Here, the rare earth permanent magnet raw material magnetic powder is a nanocrystalline magnetic powder or an amorphous magnetic powder, the average particle size of the nanocrystalline magnetic powder is 200 nm or less, the number of crystal grains of the sheet-shaped nanocrystals inside the produced precursor sheet-shaped nanocrystalline magnetic powder accounts for 85% or more of the total number of crystal grains, the average particle size of the crystal grains of the sheet-shaped nanocrystals in the thickness direction is 10 to 300 nm, and the average particle size of the crystal grains of the sheet-shaped nanocrystals in the length direction is 30 to 800 nm. This is a method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material.
2. The component of the rare earth permanent magnet raw material magnetic powder is RE x Fe 100-x-y-z T.M. y B z 2. The method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 1, wherein RE is one or more of La, Ce, Pr, Nd, Y, Dy and Tb, TM is one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al and Zn, and x, y and z represent mass fractions of the elements, where 26.0≦x≦36.0, 0.14≦y≦8.0 and 0.8≦z≦1.
36.
3. S1. The manufacturing process of the precursor sheet-shaped nanocrystalline magnetic powder is to keep the rare earth permanent magnet raw material magnetic powder at a temperature of 710 ℃ to 740 ℃ for 5 to 100 minutes under vacuum or protective atmosphere to manufacture the precursor sheet-shaped nanocrystalline magnetic powder, the number of the crystal grains of the sheet-shaped nanocrystalline crystals inside the precursor sheet-shaped nanocrystalline magnetic powder accounts for more than 85% of the total number of crystal grains, the average grain size of the crystal grains of the sheet-shaped nanocrystalline crystals in the thickness direction is 50 to 150 nm, and the average grain size of the crystal grains of the sheet-shaped nanocrystalline crystals in the length direction is 150 to 600 nm according to claim 1 or 2.
4. S1. The manufacturing process of the precursor sheet-shaped nanocrystalline magnetic powder is as follows: the rare earth permanent magnet raw material magnetic powder is kept at 710℃-740℃ for 15-60min under vacuum or protective atmosphere to manufacture the precursor sheet-shaped nanocrystalline magnetic powder, the number of the sheet-shaped nanocrystalline crystal grains in the precursor sheet-shaped nanocrystalline magnetic powder accounts for more than 85% of the total number of crystal grains, the average grain size of the sheet-shaped nanocrystalline crystal grains in the thickness direction is 60-100nm, and the average grain size of the sheet-shaped nanocrystalline crystal grains in the length direction is 180-400nm.
5. The method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 4, characterized in that the number of crystal grains of the sheet-shaped nanocrystalline precursor sheet-shaped nanocrystalline magnetic powder accounts for more than 90% of the total number of crystal grains.
6. S2. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 1 or 2, characterized in that the process of hot deformation in the hot deformation orientation treatment is one or more of hot rolling deformation, hot pressing deformation and hot extrusion deformation.
7. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 6, characterized in that the hot rolling deformation process is to carry out hot rolling deformation on the precursor sheet-shaped nanocrystalline magnetic powder under vacuum or protective atmosphere to arrange the sheet-shaped nanocrystals regularly, the temperature of the hot rolling deformation is 600-850°C, and the deformation amount of the precursor sheet-shaped nanocrystalline magnetic powder in the thickness direction is 50-90%.
8. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 7, characterized in that the temperature of the hot rolling deformation is 750-850°C, and the deformation amount in the thickness direction of the precursor sheet-shaped nanocrystalline magnetic powder is 60-80%.
9. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 6, characterized in that the hot press deformation process is to vacuum seal the precursor sheet-shaped nanocrystalline magnetic powder using a sealant to obtain a sealed body, and then to perform hot press deformation on the sealed body at a temperature of 600 to 850°C to arrange the sheet-shaped nanocrystals regularly, the hot press deformation speed is 0.02 to 3 mm / s, and the deformation amount of the sealed body in the hot press direction is 50 to 90%.
10. 10. The method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 9, wherein the sealing material is a plastic material.
11. The method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 9, characterized in that the temperature of the hot press deformation is 700-850°C, the deformation amount of the sealing body in the hot press direction is 60-80%, and the speed of the hot press deformation is 0.02-1.00 mm / s or 1.00-3.00 mm / s.
12. The hot press deformation process is characterized in that the precursor sheet-shaped nanocrystalline magnetic powder is manufactured into a base material with a density of 65.0% to 99.9% at room temperature to 800°C, and the base material is subjected to hot press deformation to arrange the sheet-shaped nanocrystals regularly, the hot press deformation temperature is 600 to 850°C, the deformation amount of the base material in the hot press direction is 50 to 90%, and the hot press deformation speed is 0.02 to 3 mm / s.
13. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 12, characterized in that the temperature of the hot press deformation is 700-850°C, the deformation amount of the base material in the hot press direction is 60-80%, and the speed of the hot press deformation is 0.02-1.00 mm / s or 1.00-3.00 mm / s.
14. The hot extrusion deformation process is characterized in that the precursor sheet-shaped nanocrystalline magnetic powder is manufactured into a base material with a density of 65.0% to 99.9% at room temperature to 800°C, and then the base material is subjected to hot extrusion deformation to arrange the sheet-shaped nanocrystals regularly, the temperature of the hot extrusion deformation is 600 to 850°C, and the speed of the hot extrusion deformation is 0.02 to 3 mm / s.
15. The method for producing anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to claim 1, characterized in that in the S3. orientation optimization post-treatment, the heat-retention temperature is 750-850°C, and the heat-retention time is 5-60 min.
16. An anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material obtained by the method for producing an anisotropic sheet-shaped nanocrystalline rare earth permanent magnet material according to any one of claims 1 to 15.
17. The anisotropic sheet-shaped nanocrystal rare earth permanent magnet material according to claim 16, characterized in that the anisotropic sheet-shaped nanocrystals have an average grain size in the thickness direction of 30 to 200 nm and an average grain size in the length direction of 150 to 800 nm.
Citation Information
Patent Citations
Manufacturing method of anisotropic rare earth magnet
JP2012023190A
Manufacturing method of rare earth magnet
JP2012244111A
Method for manufacturing oriented magnet
JP2015050427A
Method for manufacturing neodymium-iron-boron based magnet
JP2019186331A
Manufacturing method of rare-earth magnet
JP2022093885A
